2018
DOI: 10.1371/journal.pone.0193182
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 2 is a molecular bridge linking telomerase and autophagy

Abstract: Autophagy is systematically regulated by upstream factors and nutrients. Recent studies reported that telomerase and hexokinase 2 [HK2) regulate autophagy through mTOR and that telomerase has the capacity to bind to the HK2 promoter. However, the molecular linkage among telomerase, HK2, and autophagy is not fully understood. Here, we show that HK2 connects telomerase to autophagy. HK2 inhibition in HepG2 cells suppressed TERT-induced autophagy activation and further enhancement by glucose deprivation. The HK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Because TERT and autophagy gain of function have been observed in several cancers, we proposed a model in which TERT activates autophagy, which is important for generating essential nutrients in a metabolically challenged tumor microenvironment, such as hypoxia (26,27). Thus, we further measured the expression level of LC3-II, a microtubule-associated protein that is a key marker of autophagy, by immunohistochemical staining analysis in 75 PTC patients.…”
Section: Lc3-ii Is Overexpressed In Ptc Tissues and Positively Associmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TERT and autophagy gain of function have been observed in several cancers, we proposed a model in which TERT activates autophagy, which is important for generating essential nutrients in a metabolically challenged tumor microenvironment, such as hypoxia (26,27). Thus, we further measured the expression level of LC3-II, a microtubule-associated protein that is a key marker of autophagy, by immunohistochemical staining analysis in 75 PTC patients.…”
Section: Lc3-ii Is Overexpressed In Ptc Tissues and Positively Associmentioning
confidence: 99%
“…Thus, TERT plays a critical role not only in cell survival but also in metabolism. Studies have indicated that gain of TERT function modulates the activity of the mammalian target of rapamycin (mTOR) and induces autophagy, which is required for metabolic rewiring, to scavenge the nutrients that are necessary for fueling cancer cell growth in a challenging tumor microenvironment (26,27). Increasing studies have supported the central role of autophagy in the maintenance and development of various kinds of cancers, including thyroid carcinoma (28).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism may be mediated in part by increased mTOR signalling 20 . A recent study reported that TERT can promote autophagy in cancer cells under glucose deprivation through an HK2-mTOR pathway 21 . Our study also revealed that TERT can increase the autophagy activity of myocardial cells after myocardial ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…RNA purification and cDNA synthesis were performed as described previously [56]. Briefly, total RNA was isolated using TRIzol reagent (Ambion, Life technologies, USA), following which cDNA was synthesized using a RevertAid First strand cDNA Synthesis Kit (Thermo Fisher Scientific Inc, USA).…”
Section: Rna Purification and Real-time Quantitative Pcr Analysismentioning
confidence: 99%